Chemoradiotherapy vs radiotherapy for nonoperative early stage esophageal cancer: A seer data analysis. (22nd May 2020) - Li, Jiaxin; Jia, Yibin; Cheng, Yufeng; Wang, Jianbo
Abstract: Background: The benefit of endoscopic treatment (ET) and esophagectomy for early esophageal cancer (EC) has been sufficiently recognized. Radiotherapy (RT) is the main treatment modality for patients who do not undergo surgery. The effectiveness of adding chemotherapy (CT) to RT remains unclear. This study aimed to evaluate the impact of chemoradiotherapy (CRT) and RT alone on overall survival (OS) and cancer‐specific survival (CSS) in early EC patients not undergoing surgery. Methods: Data collected between 2004 and 2015 were obtained from the national Surveillance, Epidemiology, and End Results (SEER) database. All the samples were randomly grouped into the training cohort or the verification cohort. The training cohort was split into subgroups by stage, age, and histology. Stage was based on the American Joint Committee on Cancer (AJCC) 6th edition published in 2004. The Kaplan‐Meier method and Cox proportional hazards modeling were used to compare OS and CSS. The performance of the nomogram was measured by a concordance index (C‐index) and the calibration curve. Results: Data for a total of 5332 patients were obtained from the SEER database. A total of 3736 patients (stage I: n = 1277; stage IIA: n = 1484; stage IIB: n = 975) were used for the training cohort. Multivariate Cox regression analysis showed that age, sex, histology, grade, therapy, reasons for no surgery, and year of diagnosis were independent predictors of OS. The survival curve of patients treated with CRT showed a significant survival benefit compared to that in patients treated by RT alone in stage I, stage IIA, and stage IIB. CRT was also found to be related to better survival than RT in patients at a younger age (<65) and an older age (≥65) with squamous cell carcinoma or adenocarcinoma. Conclusions: Compared with RT, CRT results in better OS and CSS in early EC patients who do not undergo surgery. Abstract : Chemoradiotherapy results in a better OS and CSS in early esophageal cancer patients who do not undergo surgery.